2008
DOI: 10.1080/01495730802194425
|View full text |Cite
|
Sign up to set email alerts
|

Analytical Models of Thermal-Stress Induced Phenomena in Isotropic Multi-Particle-Matrix System

Abstract: The paper presents four topics dealing with phenomena induced by elastic thermal stresses acting in an isotropic multi-particle-matrix system to represent a model system applicable to real multi-phase materials of a precipitation-matrix type. The isotropic multi-particle-matrix system consists of periodically distributed spherical particles in an infinite matrix to be imaginarily divided into cubic cells containing a central spherical particle. Formulae for the thermal stresses to be investigated within the cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 28 publications
(75 reference statements)
0
3
0
Order By: Relevance
“…The obtained composites had high fracture toughness and high tribological performance [10]. Several papers have also reported that the tribological properties of carbon based materials such as graphite, diamond-like carbon (DLC) and cluster diamond make them promising as low friction materials [11][12][13][14][15]. In this work silicon nitride based composites with 3 wt% different carbon additives (CNT, graphene and carbon black) have been prepared.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained composites had high fracture toughness and high tribological performance [10]. Several papers have also reported that the tribological properties of carbon based materials such as graphite, diamond-like carbon (DLC) and cluster diamond make them promising as low friction materials [11][12][13][14][15]. In this work silicon nitride based composites with 3 wt% different carbon additives (CNT, graphene and carbon black) have been prepared.…”
Section: Introductionmentioning
confidence: 99%
“…Several papers have also reported that the tribological properties of carbon based materials such as graphite, DLC and cluster diamond make them promising as low friction materials. [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Strength of ceramic materials is usually determined by three-or four-point bending tests representing standard experimental techniques to induce a quasi-uniaxial stress state with insignificant stress gradients. On the other hand, mechanical loading within practical applications is usually represented by a multi-axial and non-homogeneous stress state with significant stress gradients [5]- [7]. The multi-axial and non-homogeneous stress state can be induced by line or point contact loading obtained by two opposite rollers or spheres, respectively.…”
Section: Introductionmentioning
confidence: 99%